(3TQM efGRd GdSGFQjfs - (3YHO GdZfj GdJdeSGfis; (3GdgQhj , YHO Gddg Hf eMeO Hf Ydj GdCfUGQj GdgQhj, CHh ESeGYjd,J (B481 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi GSJNQJ Gddg JYGdi bGd GdTjN QVj Gddg Yfg ai Chd cJGHg gPG GdMeO ddg Gddg gh GSe ddPGJ GdYdjI GdTQjaI dG HEYJHGQ UaI ajgG s
(3BNQgG (B:s
(3hSHH chfg eTQc Cfg ESJfO Edi fRGgI GdMb eG dG jdjb Hg ESfGOg aEf MVQI CRdjJg JCHi fWb GdMOK hGddg ef hQGFge eMjW s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJUha hGdBOGH GdTQYjIs